Insights into the mechanisms of Cronobacter sakazakii virulence - Phair, Katie (2022)
Cronobacter species have adapted to survive harsh conditions, particularly in the food manufacture environment, and can cause life-threatening infections in susceptible hosts. These opportunistic pathogens employ a multitude of mechanisms to aid their virulence throughout three key stages: environmental persistence, infection strategy, and systemic persistence in the human host. Environmental persistence is aided by the formation of biofilms, development of subpopulations, and high tolerance to environmental stressors. Successful infection in the human host involves several mechanisms such as protein secretion, motility, quorum sensing, colonisation, and translocation. Survival inside the host is achieved via competitive acquisition and utilization of minerals and metabolites respectively, coupled with host immune system evasion and antimicrobial resistance (AMR) mechanisms. Across the globe, Cronobacter sakazakii is associated with often fatal systemic infections in populations including neonates, infants, the elderly and the immunocompromised. By providing insight into the mechanisms of virulence utilised by this pathogen across these three stages, this review identifies current gaps in the literature. Further research into these virulence mechanisms is required to inform novel mitigation measures to improve global food safety with regards to this food-borne pathogen.